SEROTONIN SYNDROME IN A PATIENT WITH DUAL DIAGNOSIS-CASE STUDY - Cvjetković Bošnjak, Mina; Bibić, Željko; Kuljančić, Dušan (Sanamed, 2023)
Introduction: Serotonin syndrome is a rare but potentially life-threatening condition. In most cases, this complication is caused by taking two serotonergic medications simultaneously, leading to excessive serotonin concentration in the body. Selective serotonin reuptake inhibitors (SSRIs), selective serotonin and norepinephrine reuptake inhibitors (SNRIs), as well as irreversible monoamine oxidase inhibitors (MAOIs) and their combination with other serotonergic substances, are associated with symptoms of serotonin syndrome. Case study: A patient who was prescribed sertraline (an SSRI) for a depressive episode suffered fractures in a traffic accident during the treatment, and tramadol was prescribed for her pain. Since both drugs tend to increase serotonin levels in the body, a complication in the form of serotonin syndrome developed. With timely recognition and treatment, the symptoms of serotonin syndrome resolved without lasting consequences. Conclusion: Numerous drugs and substances can induce serotonin syndrome, often in combination with antidepressants. Therefore, it is of great importance that doctors are aware of comorbid conditions that necessitate the use of the mentioned drugs in order to prevent serotonin syndrome. If it does occur, adequate and successful treatment is crucial.